2016
DOI: 10.1002/jmri.25442
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of global cerebral blood flow measured by phase‐contrast mapping MRI with 15O‐H2O positron emission tomography

Abstract: PurposeTo compare mean global cerebral blood flow (CBF) measured by phase‐contrast mapping magnetic resonance imaging (PCM MRI) and by 15O‐H2O positron emission tomography (PET) in healthy subjects. PCM MRI is increasingly being used to measure mean global CBF, but has not been validated in vivo against an accepted reference technique.Materials and MethodsSame‐day measurements of CBF by 15O‐H2O PET and subsequently by PCM MRI were performed on 22 healthy young male volunteers. Global CBF by PET was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
54
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 47 publications
10
54
2
Order By: Relevance
“…Lastly, velocity encoding was set to 80 cm/s (24) in order to measure both low and high flows at hypo-and hypercapnia, respectively. A recent study comparing CBF measurements from PC MRI and 15 O-water PET in healthy human subjects reported only a moderate correlation between the 2 techniques and significantly higher values from PC MRI-up to a 63% overestimation (38). This result is in contrast to the current study, in which a strong correlation was found (slope, 0.88; intercept, 1.7 mL/100 g/min; R 2 5 0.9 [ Fig.…”
Section: Discussioncontrasting
confidence: 96%
“…Lastly, velocity encoding was set to 80 cm/s (24) in order to measure both low and high flows at hypo-and hypercapnia, respectively. A recent study comparing CBF measurements from PC MRI and 15 O-water PET in healthy human subjects reported only a moderate correlation between the 2 techniques and significantly higher values from PC MRI-up to a 63% overestimation (38). This result is in contrast to the current study, in which a strong correlation was found (slope, 0.88; intercept, 1.7 mL/100 g/min; R 2 5 0.9 [ Fig.…”
Section: Discussioncontrasting
confidence: 96%
“…Furthermore, the 4D-CTA flow rates indicate an average global cerebral blood flow (CBF) of 545 AE 78 ml/min. This is in good agreement with a recent PET study (503 ml/min), 27 which also pointed out discrepancies with PCMRI data neglecting partial volume effects.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, comparisons with cerebral blood flow rate (CBF) assessed with positron emission tomography (PET) in Ref. showed recurrent overestimation of 2D‐PCMRI measurements. These results emphasize the importance to correct these biases independently of the spatial resolution.…”
Section: Discussionmentioning
confidence: 98%
“…Mainly tested on 2D‐PCMRI datasets, these post‐processings require the localization of the circulating volume or assume idealized velocity profiles (typically parabolic Poiseuille flow) which are in general erroneous. Previous in vitro and recent in vivo studies have shown that these partial volume effects might lead to blood flow rate overestimation. However, these effects were not considered in most of the recent intracranial flow investigations .…”
Section: Introductionmentioning
confidence: 99%